Culture, Spirituality and Religious Literacy in Healthcare - Enstedt, Daniel; Dellenborg, Lisen (Taylor & Francis, 2024)
Elaborating with the concepts of culture and religious literacy, this volume examines theoretical, methodological and empirical aspects of the practice and study of religion and non-religion, culture, spirituality and worldviews within healthcare. In modern multi-cultural and multi-religious societies, a host of new issues have arisen concerning culture, religion and spirituality within healthcare, especially when people face serious and life-limiting illness. Healthcare professionals are faced with challenges addressing and handling patients? cultural expressions of religiosity, spirituality and existential concerns. The variety needs to be met without essentializing the concepts of culture and religion, and with an ability to include the non-religious as well as new types of spiritualities. This collection reﬂects on the tension between cultural, religious and spiritual dimensions of care in a secularized healthcare institution and describes implications of this tension for healthcare professionals and patients. The book engages with an ongoing scholarly discussion about religious literacy in healthcare, and contributes perspectives, experiences and empirical examples from the Nordic countries, especially Sweden. It gives suggestions for practical application of research to healthcare practice, highlighting challenges and ideas for how to integrate religious, non-religious, and spiritual dimensions in care. This is an important contribution to the literature on religious literacy and provides a vital reference for students, scholars and healthcare professionals with an interest in the complex relationship between culture, spirituality, and religion in healthcare.